2023
DOI: 10.1002/dvdy.569
|View full text |Cite
|
Sign up to set email alerts
|

Colec12 and Trail signaling confine cranial neural crest cell trajectories and promote collective cell migration

Abstract: Background Collective and discrete neural crest cell (NCC) migratory streams are crucial to vertebrate head patterning. However, the factors that confine NCC trajectories and promote collective cell migration remain unclear. Results Computational simulations predicted that confinement is required only along the initial one‐third of the cranial NCC migratory pathway. This guided our study of Colec12 (Collectin‐12, a transmembrane scavenger receptor C‐type lectin) and Trail (tumor necrosis factor‐related apoptos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Often, hypotheses generated in silico are used to predict key parameters or mechanisms within a system, which in turn expedite corresponding experimental investigations by reducing their required scope. For example, the ABM for NCC migration considered by McLennan et al (2023) was used to predict that Trail and Colec12, factors expressed adjacent to the pathways along which cranial NCCs migrate in chick, must only be highly expressed for a fraction of the regions adjacent to NCC collectives for the restriction of NCC movement to stereotypical migratory pathways. This hypothesis was then tested in chick, where Colec12 and Trail were also found to be highly expressed for around one-third of the regions adjacent to the pathways along which NCC migration occurs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Often, hypotheses generated in silico are used to predict key parameters or mechanisms within a system, which in turn expedite corresponding experimental investigations by reducing their required scope. For example, the ABM for NCC migration considered by McLennan et al (2023) was used to predict that Trail and Colec12, factors expressed adjacent to the pathways along which cranial NCCs migrate in chick, must only be highly expressed for a fraction of the regions adjacent to NCC collectives for the restriction of NCC movement to stereotypical migratory pathways. This hypothesis was then tested in chick, where Colec12 and Trail were also found to be highly expressed for around one-third of the regions adjacent to the pathways along which NCC migration occurs.…”
Section: Discussionmentioning
confidence: 99%
“…A later developed hybrid model for collective migration in the chick cranial neural crest represents the ECM via a tunneling mechanism, in which follower cells move along tunnels of aligned ECM formed by leader cells (McLennan et al, 2023). This model was used highlight the importance of spatial confinement in chick cranial NCC migration, suggesting that factors such as Colec12 and Trail, which are expressed primarily in NCC-free zones adjacent to NCC collectives, play a key role in confining NCCs to stereotypical migratory pathways during migration and maintaining coherence within collectives.…”
Section: Neural Crest Cell (Ncc) Migrationmentioning
confidence: 99%
“…more tightly controlled parameters or reinforcement through environmental heterogeneity. A number of modelling and experimental studies have suggested that microenvironmental factors may indeed play an important role in confining collective migration of neural crest cells along particular pathways [49, 50].…”
Section: Discussionmentioning
confidence: 99%
“…McLennan et al. ( 117 ), based on computational analysis and data from an animal model (chick embryo), found CL-12 contributed to cranial neural crest cell trajectories and promoted collective cell migration. Recently, Ajami et al.…”
Section: Clinical Associations Of Collectins In the Neonatementioning
confidence: 99%
“…On the other hand, like CL-10 and CL-11, it is considered crucial for ontogenesis. McLennan et al (117), based on computational analysis and data from an animal model (chick embryo), found CL-12 contributed to cranial neural crest cell trajectories and promoted collective cell migration. Recently, Ajami et al (118) described siblings (3.5 year-old girl and 10 month-old boy) with derivative chromosome 9, resulting in partial 9p monosomy and 18p trisomy.…”
Section: Collectin-10 Collectin-11 and Collectin-12mentioning
confidence: 99%